Un dispositif liant théâtre et recherche, vecteur d’une dynamique inclusive ? - Claire de Saint Martin; Marie Astier (Éducation et Socialisation)
Since August 2017, we have been carrying out a research and theatre project about inclusion, based on theatre workshops that bring together participants with and without disabilities. Theatre training, which focuses on choral work, is combined with a collaborative research project about inclusion: the participants reflect together upon the inclusive reality they are experimenting. Collective life is ongoing since all are hosted in the same place and share the same meals. To what extent does this arrangement entail the development of an inclusive dynamic within the group? This experiment stresses the importance of combining a theatre project with a research process. It also demonstrates the crucial role of speech, in artistic creation as much as in scientific research. This experiment also shows the tensions regarding “inclusion” in a specific context, as much as it shows its actuality. This project’s contributions are twofold: the production of knowledge about inclusion, on one hand, and on theatre creation, on the other.